Mortality Among Hardmetal Production Workers: UK Cohort and Nested Case–Control Studies. Issue 12 (December 2017) - McElvenny, Damien M.; MacCalman, Laura A.; Sleeuwenhoek, Anne; Davis, Alice; Miller, Brian G.; Alexander, Carla; Cowie, Hilary; Cherrie, John W.; Kennedy, Kathleen J.; Esmen, Nurtan A.; Zimmerman, Sarah D.; Buchanich, Jeanine M.; et al.
Abstract : Objective: The aim of this study was to characterize the mortality at two hardmetal production factories in the United Kingdom as part of an international study. Methods: Standardized mortality ratios (SMRs) were calculated on the basis of mortality rates for England and Wales, and local rates. A nested case–control study of lung cancer was undertaken. Results: The cohort comprised 1538 workers, with tracing complete for 94.4%. All-cause mortality was statistically significantly low for all cancers and nonmalignant respiratory disease, and for lung cancer was nonsignificantly low. The SMR for lung cancer for maintenance workers was elevated, based on only six deaths. The odds ratio for lung cancer per year of exposure to hardmetal was 0.93 (0.76 to 1.13). Conclusions: In this small study, there is no evidence to support that working in the UK hardmetal manufacturing industry increased mortality from any cause including lung cancer.